Changes in synaptic inputs to dI3 INs and MNs after complete transection in adult mice - Goltash, Sara; Stevens, Shannon J.; Topcu, Emine; Bui, Tuan V. (Frontiers in Neural Circuits, 2023)
Introduction Spinal cord injury (SCI) is a debilitating condition that disrupts the communication between the brain and the spinal cord. Several studies have sought to determine how to revive dormant spinal circuits caudal to the lesion to restore movements in paralyzed patients. So far, recovery levels in human patients have been modest at best. In contrast, animal models of SCI exhibit more recovery of lost function. Previous work from our lab has identified dI3 interneurons as a spinal neuron population central to the recovery of locomotor function in spinalized mice. We seek to determine the changes in the circuitry of dI3 interneurons and motoneurons following SCI in adult mice. Methods After a complete transection of the spinal cord at T9-T11 level in transgenic Isl1:YFP mice and subsequent treadmill training at various time points of recovery following surgery, we examined changes in three key circuits involving dI3 interneurons and motoneurons: (1) Sensory inputs from proprioceptive and cutaneous afferents, (2) Presynaptic inhibition of sensory inputs, and (3) Central excitatory glutamatergic synapses from spinal neurons onto dI3 INs and motoneurons. Furthermore, we examined the possible role of treadmill training on changes in synaptic connectivity to dI3 interneurons and motoneurons. Results Our data suggests that VGLUT1+ inputs to dI3 interneurons decrease transiently or only at later stages after injury, whereas levels of VGLUT1+ remain the same for motoneurons after injury. Levels of VGLUT2+ inputs to dI3 INs and MNs may show transient increases but fall below levels seen in sham-operated mice after a period of time. Levels of presynaptic inhibition to VGLUT1+ inputs to dI3 INs and MNs can rise shortly after SCI, but those increases do not persist. However, levels of presynaptic inhibition to VGLUT1+ inputs never fell below levels observed in sham-operated mice. For some synaptic inputs studied, levels were higher in spinal cord-injured animals that received treadmill training, but these increases were observed only at some time points. Discussion These results suggest remodeling of spinal circuits involving spinal interneurons that have previously been implicated in the recovery of locomotor function after spinal cord injury in mice.